Reversed Brayton cycle for food freezing at very low temperatures: Energy performance and optimisation. (September 2017) - Biglia, Alessandro; Comba, Lorenzo; Fabrizio, Enrico; Gay, Paolo; Mannini, Achille; Mussinatto, Adriano; Ricauda Aimonino, Davide
Graphical Abstract: Highlights: An innovative system for food freezing at very low temperature has been designed. The system is based on a modified reversed Brayton cycle. Performance analysis results show the pressure level as a relevant parameter. The proposed system has lower running cost than liquid nitrogen plants. Abstract: Freezing is a valuable method to increase food shelf life and to ensure high quality standards during long-term storage. Additional benefits to frozen food quality can be achieved by freezing at very low temperatures (< −50 °C): small ice crystal formation during fast freezing reduces food cell wall rupture, preventing water and texture loss during thawing. This paper presents the design of an innovative food freezing system operating at very low temperatures, based on a modified reversed Brayton cycle (rB cycle). The plant is composed of two interconnected sub-systems: a primary thermodynamic closed loop, operated by an rB cycle, and a secondary airflow loop which is devoted to food freezing by batch process. Relevant features of the designed rB cycle rely on the adopted environmentally safe working fluid, the optimised thermodynamics working conditions and the innovative cycle layout. A modelling framework for the system was developed to identify and design efficient operative settings for the plant components (turbo-machineries, heat exchangers, etc.) and to assess, via sensitivity analysis, the influence of the main design parameters on the global energy performance. The proposed system configuration, designed to maximise the coefficient of performance (CoP) value of the plant, was determined by means of nonlinear multivariable optimisation. In addition, the energy performance of the system can be increased by recovering waste heat available from the rB cycle.